2018
DOI: 10.1163/1568539x-00003482
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early-life stress on the expression of HPA-associated genes in the adult murine brain

Abstract: Early life is an important period for the development of the nervous system and for the programming of behavioural phenotypes in adulthood. In our study, two types of early-life stress were used: prolonged separation of pups from their mothers (for 3 h/day, maternal separation (MS)) and brief separation (for 15 min/day, handling (HD)). We analysed the effects of early-life stress on behaviour and the expression of HPA-associated genes in the hypothalamus, hippocampus, and frontal cortex of male mice. Adult mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…Nonetheless, in our experiment, the higher Nr1d1 expression did not result in alteration of Nr3c1 or Nr3c2 expression in the prefrontal cortex and hippocampus of adult female mice. Similarly, in our recent study [61] on males, we did not detect changes in the expression of either Nr3c1 or Nr3c2 under the influence of early-life stress, in agreement with the absence of such changes in females, but prolonged maternal separation resulted in a higher Nr3c2/Nr3c1 mRNA ratio in the 6 Behavioural Neurology hippocampus and hypothalamus in males. Thus, we did not detect an influence of early-life stress on Nr3c1 or Nr3c2 expression in females, at least under unstressful conditions.…”
Section: Early-life Stress Increases the Expression Of Nr1d1 But Doessupporting
confidence: 91%
“…Nonetheless, in our experiment, the higher Nr1d1 expression did not result in alteration of Nr3c1 or Nr3c2 expression in the prefrontal cortex and hippocampus of adult female mice. Similarly, in our recent study [61] on males, we did not detect changes in the expression of either Nr3c1 or Nr3c2 under the influence of early-life stress, in agreement with the absence of such changes in females, but prolonged maternal separation resulted in a higher Nr3c2/Nr3c1 mRNA ratio in the 6 Behavioural Neurology hippocampus and hypothalamus in males. Thus, we did not detect an influence of early-life stress on Nr3c1 or Nr3c2 expression in females, at least under unstressful conditions.…”
Section: Early-life Stress Increases the Expression Of Nr1d1 But Doessupporting
confidence: 91%
“…The MS is a stress‐causative factor that has been used to create mental health disturbances in different studies, particularly studies on stress and reproductive system disorders . Furthermore, It was demonstrated that the implications from early life stress appear later in the adulthood …”
Section: Discussionmentioning
confidence: 99%
“…Many studies show the critical importance of the postnatal period for individual development because stress in this period can have delayed effects on cognition, individual behavior, neuronal plasticity and epigenetics . Nevertheless, the mouse and rat studies on MS and HD effects on cognition in adult females are limited.…”
Section: Discussionmentioning
confidence: 99%